Efficacy of low-magnitude high-frequency vibration (LMHFV) on musculoskeletal health of participants on wheelchair: a study protocol for a single-blinded randomised controlled study - Ronald Man-Yeung Wong; Simon Kwoon Ho Chow; Chung Yan Ho; Hiu Wun Wong; Yu Ning Chim; Wing Hoi Cheung (BMJ Open)
Background Osteoporosis is an age-related disease with progressive loss of bone, leading to fragile bone. It is one of the major health issues in older adults and causes medical, social and economic impacts globally. Patients with osteoporosis have high risk of osteoporotic fractures. Low-magnitude high-frequency vibration (LMHFV) is a non-invasive biophysical intervention providing whole-body mechanical stimulation. Previous studies showed that LMHFV is beneficial to muscle strength, postural control, balancing ability, new bone formation, spinal bone mineral density (BMD) and blood circulation. During the LMHFV treatment, older adults need to stand upright on the platform for 20 min/day. However, some physically weak elderlies with poor musculoskeletal ability cannot stand for a long period. Therefore, the design of vibration platform is modified for the disabled patients to treat at sitting position and the efficacy of LMHFV on this group of elderlies will be verified. It is hypothesised that new design of LMHFV is beneficial to wheelchair users in terms of vertebral BMD, muscle health and musculoskeletal functions.Methods This study is a single-blinded randomised controlled trial to investigate the effect of LMHFV on vertebral BMD, muscle health, balancing ability and functional ability in wheelchair users (mainly on wheelchair for outdoor activities). Healthy elderlies aged 65 years or above with walking difficulties and using wheelchair are eligible. Exclusion criteria are those: (1) who cannot stand and walk independently, (2) who have vibration treatment before, (3) with malignancy, (4) with acute fractures or severe osteoarthritis, (5) with cardiovascular concern such as with pacemaker in situ, (6) with chronic inflammatory conditions known to affect muscle metabolism such as rheumatoid arthritis and (7) with high frequency of physical activities, such as participants who participated in regular exercise five times a week or more. Recruited participants will be randomised to either LMHFV or control group. Participant assigned to LMHFV group will receive LMHFV (35 Hz, 0.3g (g=gravitational acceleration), 20 min/day, at least three times/week) for 6 months. The primary outcome is BMD at the lumbar spine to be assessed by dual-energy X-ray absorptiometry that is clinically recommended for the diagnosis of osteoporosis. All primary and secondary outcome assessments for all groups will be performed in the investigators’ institute at baseline and 6 months post treatment.Discussion This study aims to investigate the effects of LMHFV on wheelchair users. The findings of this study will help to confirm the efficacy of LMHFV on vertebral BMD, muscle health, balancing ability and functional outcomes in wheelchair using elderlies. LMHFV therapy is an intervention strategy that is easy to implement at the community healthcare level or individually at home that has previously been proven to reduce fall risk and muscle strength at the lower limb. The ultimate goal is to improve their bone and muscle quality of wheelchair users, as well as enhancing their quality of life.Trial registration number ClinicalTrials.gov (NCT04180267).